Inovasi pembelajaran pendidikan islam (stadi kasus di smk mambaul ulum bondowoso) - Halim, Abdul; Zaenul Fitri , Agus; Maktumah, Luluk; Maryam, Siti; Mahtum, Rohiqi; Abdul Wafa, Asyari (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
This research aims to describe the PAI learning model in improving the quality of student learning outcomes through a learning innovation approach applied by PAI teachers at Mambaul Ulum Vocational School Wonosari Bondowoso. The research approach used is phenomenology with a qualitative research type. The results of data analysis found that the implementation of learning implemented by class Meanwhile, the innovation provides additional points for students who are active in understanding the lesson material. The learning methods applied are lecture and discussion methods. Meanwhile, the innovation implemented by class XII PAI teachers is Game Based Learning (GBL) and uses lecture and discussion methods. The supporting factor that influences learning innovation by class XI PAI teachers is providing advice to students. Meanwhile, the problem is that most students don't pay attention when the teacher explains the material. Supporting factors that influence learning innovation in class XII are teacher discipline, not being long-winded in explaining the material, and safe and peaceful class conditions. The problem is that there are similarities with other classes, namely students do not pay attention when the teacher explains the material